Identification and characterization of common B cell epitope in bovine leukemia virus via high-throughput peptide screening system in infected cattle. Issue 1 (December 2015) - Bai, Lanlan; Otsuki, Hiroyuki; Sato, Hirotaka; Kohara, Junko; Isogai, Emiko; Takeshima, Shin-nosuke; Aida, Yoko
Abstract Background Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leukosis, the most common neoplastic disease of cattle. BLV is closely related to human T cell leukemia virus. B cell epitopes are important for the use of antibodies as therapeutic agents, the epitope-driven vaccine design, and immunological assays. A common B cell epitope for BLV has not yet been found due to individual differences in disease susceptibility. Results We used a peptide microarray with 156 synthetic 15-mer peptides covering the envelope glycoprotein gp51 and the Gag proteins p15, p24, and p12 to map B cell epitope and one B cell epitope, gp51p16, was recognized by all four cattle experimentally infected with BLV. A newly developed high-throughput peptide ELISA system revealed 590 (91.2 %) of 647 cattle naturally infected with BLV, carrying 25 different bovine leukocyte antigen class IIDRB3 (BoLA -DRB3) alleles, responded to a 20-mer gp51p16-C peptide containing a C-terminal cysteine and gp51p16. Alanine mutation and comparison of the sequences at 17 amino acid positions within gp51p16-C revealed that R7, R9, F10, V16, and Y18 were the common binding sites to BLV antibodies, and two of these sites were found to be highly conserved. Transient expression in the cells of five infectious molecular clones of BLV with a single alanine mutation at five common antibody binding sites had no effect syncytia formation of the gp51 protein. In addition, the mutant proteins, R7A and R9A had no effect on the expression of gp51 protein; the gp51 protein expressions of F10A, V16A and Y18A were lower than that of the wild type protein. Conclusions This is the first report to identify a common B cell epitope in BLV by comprehensive screening of BLV-infected cattle with varied genetic backgrounds inBoLA -DRB3 . Our results have important implications for disease control and diagnosis.